2016
DOI: 10.17925/ohr.2016.12.01.51
|View full text |Cite
|
Sign up to set email alerts
|

Is Gastrointestinal Metastasis of Primary Lung Malignancy as Rare as Reported in the Literature? A Comparison Between Clinical Cases and Post-mortem Studies

Abstract: Lung cancer is a common malignancy, with metastasis occurring in approximately half of all cases. Most commonly, these secondary lesions present in the lymph nodes, adrenal glands, liver, bone, and brain. The incidence of metastatic lesions to the gastrointestinal tract is under speculation as it had originally been thought exceedingly rare. However, post-mortem studies have revealed that these secondary lesions may be more common than previously believed. This article reviews the literature regarding primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…The incidence of gastrointestinal metastasis of primary lung cancer ranges from 0.3 to 1.7% [ 7 ]; however, in postmortem studies, the incidence ranges from 4.6 to 14% [ 7 , 8 ]. This discrepancy indicates that most of the patients have asymptomatic gastrointestinal metastases.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The incidence of gastrointestinal metastasis of primary lung cancer ranges from 0.3 to 1.7% [ 7 ]; however, in postmortem studies, the incidence ranges from 4.6 to 14% [ 7 , 8 ]. This discrepancy indicates that most of the patients have asymptomatic gastrointestinal metastases.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (HIPEC) in unconventional indications is occasionally reported in experienced tertiary centers [2], most frequently from rare ovarian cancers, sarcoma, or neuroendocrine tumors, and, more rarely, from gastrointestinal stromal tumor (GIST), hepatocellular and cholangiocarcinoma and desmoplastic small round cell tumors. The gap existing between the small reported series data and the incidence rates in autopsy series could suggest that in most cases peritoneal metastases from lung cancer remain clinically silent [16]. Our results on these two patients might help in stimulating more awareness of this condition and in suggesting a strict follow-up: in fact, early diagnosis of peritoneal diffusion, which is probably often underrated, could allow a radical cytoreductive surgery providing some advantages to survival.…”
Section: Discussionmentioning
confidence: 81%
“…The prognosis for patients with peritoneal metastases from lung cancer is very poor regardless of the treatment, with a median survival rate of 2 to 4 months. In a recent review, Balla et al found two cases of peritoneal metastases out of a sample of 91 patients with lung cancer with gastrointestinal metastases: the disparity with autopsy series suggests that most cases are asymptomatic or unreported [16, 17]. Emergency surgery for bowel obstruction and extra-abdominal metastases, found in up to 60% of patients [11, 12], could be the main reasons for the poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients with intestinal metastases from primary lung are asymptomatic. 6 This finding has led to a discrepancy between the estimated incidence in clinical and postmortem studies. 18 This clinical underdiagnosis likely occurs because the intestinal symptoms experienced by the patient overlap with the adverse effects of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have reported that GI metastases from primary lung cancer are infrequent, with an incidence ranging between 0.3% and 1.7%. 6 Intestinal metastases may be asymptomatic and include obstruction, perforation, occult bleeding, and intussusception. Symptomatic intestinal metastases may be life-threatening and necessitate emergency surgery.…”
Section: Introductionmentioning
confidence: 99%